The complete chloroplast genome of Prunus conradinae (Rosaceae), a wild flowering cherry from China - Yan, Jiawen (Mitochondrial DNA B Resour, 2020)
Prunus conradinae is a flowering cherry species with high ornamental value. In this study, the complete chloroplast (cp) genome of P. conradinae was obtained using a genome skimming approach. The cp genome was 158,019 bp long, with a large single-copy region of 85,910 bp and a small single-copy region of 19,247 bp separated by two inverted repeats of 26,431 bp. It encodes 130 genes, including 85 protein-coding genes, 37 tRNA genes, and eight ribosomal RNA genes. The phylogenetic analysis indicated that P. conradinae is closely related to the congeners P. maximowiczii, P. takesimensis, P. speciosa, P. serrulata var. spontanea, P. discoidea, and P. matuurai.